Mycofactories. - Leitão, Ana Lúcia Monteiro Durão (Bentham Science Publishers, 2011)
Fungi are extremely versatile microorganisms as a biotechnology tool having the advantage of being relatively easy to grow, thus making them suitable for large scale production. Fungi have been successfully employed for biotransformations ranging from food manufacturing to drug design. Mycofactories comprise a substantial share of significant current research in the area of fungal biotechnology, and constitutes an effort to compile high level research in this domain. Topics include applications of fungi as a main source for the production of enzymes, manufacture of food derivatives, pigments a.